Analysis of the Effect of Promotion and Brand Image on Customer Purchase Decisions - Muhammad Ali Akbar; Sri Rezeki; Gustina (LPPM STIE EKA PRASETYA, 2022)
This study aims to determine the effect of Promotion on customer Purchasing Decisions Roman ceramic brand in CV. Kharisma Jaya, determine the effect of Brand Image on customer Purchasing Decisions of Roman ceramic brand in CV. Kharisma Jaya, determine the effect of Promotion and Brand Image on customer Purchasing Decisions Roman ceramic brand at CV. Kharisma Jaya. The population in this study is the customer at CV. Kharisma Jaya as many as 68 respondents. The results showed that Promotion and Brand Image partially have a positive and significant effect on customer purchasing decisions of Roman brand ceramic in CV. Kharisma Jaya. The results showed that simultaneously Promotion and Brand Image have positive and significant effect on customer Purchasing Decision of Roman brand ceramic in CV. Kharisma Jaya. The results of this study are supported by the value of R square (R2) which means that Promotion and Brand Image have an effect on Purchasing Decisions. While the rest is effected by other factors originating from outside this research model such as price and perception.